SOLUSI POLINOMIAL TAYLOR PERSAMAAN DIFERENSIAL-BEDA LINEAR DENGAN KOEFISIEN VARIABEL - Nurjanah, Siti; M., Imran; M., Musraini (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses how to obtain the Taylor polynomial solution of a higher order linear differential and difference equation with variable coefficients whose initial conditions are known. The process begins by assuming the solution of a higher order linear differential and difference equation in the form of polynomial Taylor. Then it is followed by presenting this equation and its initial conditions in the form of a matrix. This matrix is changed into an augmented matrix. Taylor polynomialsolutions of a higher order linear differential and difference equations is obtained by solving the augmented matrix using elementary row operations.